School operational Assistance Funds and Grants: Improving the Quality of Religious Education Institutions in West Kalimantan - Yapandi Yapandi; Erwin Mahrus (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2022)
This study discusses the use of school operational assistance funds and grants in improving the quality of religious education institutions in West Kalimantan. The research used is qualitative research, as for the purpose of qualitative research to understand the object under study in depth and naturally. The approach used is phenomenological approach and descriptive analysis. The meaning of Phenomenology is knowledge that is visible or refers to physical phenomena. The results of this study showed that most respondents felt the use of school operational assistance funds (BOS) and grants. It seems that the government's policy has been going well and transparently. The use of BOS Funds and Grants comes from the Government in the form of land expansion and receives direct assistance from school operational assistance. This also takes place with the quality assurance of Religious Education Institutions. Related to Quality Assurance, Religious Education Institutions at least began to get their welfare such as Benefits, Incentives, Decent Honors and the existence of Transportation money.